HPV detection and genotyping in vulvar squamous cell carcinoma in Northern Thailand - Sumalee Siriaunkgul (2018)
Background: The study was aimed to evaluate the prevalence and genotype distribution of HPV infection in vulvar squamous cell carcinoma (SCC) in northern Thailand and the clinicopathological difference with regard to HPV infection status. Materials and Methods: Formalin-fixed paraffin-embedded tissue samples of vulvar SCC diagnosed between January 2006 and December 2012 were collected. HPV infection was detected by nested polymerase chain reaction (PCR) with primers MY09/11 and GP5+/6+. HPV genotyping was performed using the Linear Array Genotyping Test, followed by type-specific PCR targeting the E6/E7 region of HPV16/18/52 if the Linear Array test was negative. The histologic slides of vulvar lesions and the medical records were reviewed. Results: There were 47 cases of vulvar SCC included in the study (mean patient age 57.9±13.2 years). HPV infection was detected in 29 cases (62%), all of which had single HPV infections. HPV16 accounted for 23 (49%). The patients with HPV-positive SCC had a significantly younger mean age than those with HPV-negative tumors (52.7 years vs 66.2 years, p < 0.001). There was no significant difference in tumor stage distribution with regard to the status of HPV infection. The presence of vulvar intraepithelial neoplasia (VIN) of usual type (basaloid or warty) was significantly more frequent in HPV-positive cases compared with HPV-negative cases (62% vs 6%, p < 0.001), whereas differentiated-type VIN was more common in HPV-negative cases (24% vs 0%, p=0.019). Conclusions: HPV infection was detected in 62% of vulvar SCC in northern Thailand. HPV16 was the predominant genotype similar to the data reported from other regions. HPV-positive SCC occurred in younger patients compared with HPV-negative SCC, and was associated with usual-type VIN. Vaccination against HPV16/18 may potentially prevent almost one half of vulvar SCC in northern Thailand.